metodicheskie perspektivy realizatsiya novykh tekhnologii obucheniya dvizheniyam i covershenstvovaniya v nikh - Dobrovolsky, S. S.; Tyutukov, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The purpose of this paper was to discuss the methodology of development professor I.P. Ratov's ideas, lying in the basis of his conception of the "artificially controlling environment (ACE) in new technologics of teaching and improvement in movements . The authors consider the difficulties of this conception's acknowledgement. The offered by authors training machine stand opens the new perspectives to use the "psychobiomechanical approach" for express-correction of the sports technique characteristics, that creates quite new situation in the didactic construction of the teaching process.